Anemia, hematinic deficiencies, hyperhomocysteinemia, and gastric parietal cell antibody positivity in burning mouth syndrome patients with macrocytosis - Ying-Tai Jin; Yu-Hsueh Wu; Yang-Che Wu; Julia Yu-Fong Chang; Chun-Pin Chiang; Andy Sun (Elsevier, 2021)
Background/purpose: Macrocytosis is defined as having the mean corpuscular volume (MCV) ≥ 100 fL. This study evaluated whether 46 burning mouth syndrome (BMS) patients with macrocytosis had significantly higher frequencies of anemia, hematinic deficiencies, hyperhomocysteinemia, and serum gastric parietal cell antibody (GPCA) positivity than 442 healthy control subjects or 884 BMS patients. Materials and methods: Complete blood count, serum iron, vitamin B12, folic acid, homocysteine, and GPCA levels in 46 BMS patients with macrocytosis, 884 BMS patients, and 442 healthy control subjects were measured and compared. Results: We found that 65.2%, 23.9%, 47.8%, 0.0%, 60.9%, and 45.7% of 46 BMS patients with macrocytosis were diagnosed as having blood hemoglobin, iron, vitamin B12, and folic acid deficiencies, hyperhomocysteinemia, and serum GPCA positivity, respectively. Moreover, 46 BMS patients with macrocytosis had significantly higher frequencies of blood hemoglobin and serum vitamin B12 deficiencies, hyperhomocysteinemia, and serum GPCA positivity than 442 healthy control subjects or 884 BMS patients (all P-values < 0.001). In addition, 46 BMS patients with macrocytosis also had a significantly higher frequency of serum iron deficiency than 442 healthy control subjects (P < 0.001). Pernicious anemia was found in 15 BMS patients with macrocytosis. Conclusion: There are significantly higher frequencies of anemia and serum iron and vitamin B12 deficiencies, hyperhomocysteinemia, and serum GPCA positivity in BMS patients with macrocytosis than in healthy control subjects. BMS patients with macrocytosis also have significantly higher frequencies of anemia, serum vitamin B12 deficiency, hyperhomocysteinemia, and serum GPCA positivity than BMS patients.